Notes on the cult of the fifteen Tiberioupolitan martyrs in medieval Bulgaria - Чешмеджиев, Димо; Kasabova, Anita (Studia Ceranea, 2011)
The cult of the fifteen Tiberioupolitan martyrs is one of the most intriguing cults in medieval Bulgaria. There are, however, a lot of questions about this cult, some of which I address in this paper. The earliest evidence of the cult is their mention in the Evangelarium Assemani (late 10th – early 11th C ), at 29th August, but only three of the martyrs are listed. Another important source for this cult is the well-known Life of Clement of Ohrid by Theophylact of Ohrid, called The martyrdom of the fifteen Tiberioupolitan martyrs (late 11th or early 12th C ). One of the most interesting evidences, however, is the very discovery of the relics, dated back to the reign of khan Boris I (852–889), when the relics proved miraculous. According to the recent studies, the cult of the fifteen martyrs was wide-spread in the region of Stroumitsa and the name of the town where the relics were placed, did not change due to them but due to a historical factor – someone called Tiberius. On the other hand, however, no Greek manuscripts mention the martyrs, except those coming from the diocese of the Ohrid archbishopry. The facts shown above proves that the cult was imported soon after the baptizing of the Bulgarians.